2005
DOI: 10.1086/497694
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Early Spread of Chloroquine‐ResistantPlasmodium falciparumInfections in Papua New Guinea

Abstract: The first report of Plasmodium falciparum chloroquine (CQ) resistance (CQR) in Papua New Guinea (PNG) appeared in 1974. Although the current prevalence of CQR-associated parasite gene polymorphisms has been documented for some regions, the spatial and temporal relationships that characterize CQ-resistant parasites in PNG are unknown. Insight into the evolution of CQ-resistant parasites could be provided by evaluating genetic markers in parasite populations. We compared pfcrt and pfmdr1 polymorphisms and flanki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
5
23
0
Order By: Relevance
“…Only 7% of the parasites carried the wild-type pfcrt CVMNK mutation (codons 72 to 76) associated with a CQ-sensitive phenotype. This high prevalence of the resistant K76T polymorphism concurred with data from studies conducted between 2000 and 2005 in Madang and East Sepik Provinces (5,28,41 (codons 72 to 76) is at fixation in the PNG parasite population, with an increase in prevalence from 83% from the early 1990s to 92.3% in 2003 to 2005 (25,27,42). Another CQ-resistant haplotype, CVIET (codons 72 to 76), found commonly in Africa and Southeast Asia (22,23,32,48), was detected in two isolates as a mixed infection with the SVMNT strain, confirming its recent emergence in PNG (10).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Only 7% of the parasites carried the wild-type pfcrt CVMNK mutation (codons 72 to 76) associated with a CQ-sensitive phenotype. This high prevalence of the resistant K76T polymorphism concurred with data from studies conducted between 2000 and 2005 in Madang and East Sepik Provinces (5,28,41 (codons 72 to 76) is at fixation in the PNG parasite population, with an increase in prevalence from 83% from the early 1990s to 92.3% in 2003 to 2005 (25,27,42). Another CQ-resistant haplotype, CVIET (codons 72 to 76), found commonly in Africa and Southeast Asia (22,23,32,48), was detected in two isolates as a mixed infection with the SVMNT strain, confirming its recent emergence in PNG (10).…”
Section: Discussionsupporting
confidence: 84%
“…Most others carried the N86Y polymorphism with the YYSND haplotype (codons 86, 184, 1034, 1042, and 1246), associated with CQ resistance. Our results reflect an increase in the frequency of this haplotype since the mid-1990s (28,29). We also observed four isolates (2%) that carried the Y184F and N1042D double point mutations, confirming the recent emergence of these pfmdr1 polymorphisms in PNG (25).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…One likely influence is the history of AQ and CQ use in these regions and the consequent selective pressure for pfcrt and pfmdr1 polymorphisms of one type or another. Haplotypes of pfcrt-encoding polymorphisms similar to those of the pfcrt alleles in South America and PNG have been reported from East Timor, Indonesia, the Philippines, Laos, India, and Iran (40)(41)(42)(43)(44)(45)(46)(47)(48)(49). In many of these regions AQ was widely used in the 1940s (50) and early 1950s before the advent of CQR (Fig.…”
Section: G8mentioning
confidence: 76%
“…2) also supports the identification of the 4-locus haplotype 3_6_3_5 as the founder. In a previous study in which we analyzed samples collected in PNG between 1982 and 1984 (during the early years of the spread of CQR in PNG), we observed that 97% of the samples carried the SVMNT1 allele and 83% of those samples carried the 3_6_3_6_10 haplotype (35). The present predominant 3_6_3_5_10 haplotype can be derived from the earlier predominant 3_6_3_6_10 haplotype by just a one-step mutation.…”
mentioning
confidence: 82%